Mewujudkan Keadilan, Kepastian dan Kemanfaatan Hukum dalam Qanun Bendera dan Lambang Aceh - Muhammad Ridwansyah (Jurnal Konstitusi, 2016)
Article 246 paragraph (2) of Law No. 11 Year 2006 concerning Aceh Government may stipulate that the Aceh government and the Aceh region determine the flag and emblem that reflects the privileges and specificity. It is indeed the opposite opinion with the provision of Article 6 (4) of Governement Regulation No. 77 Year  2007 on Regional Symbols which states that the logo design of regional flag should not have similarity in its essential part or in its entirety with logo design and the flag of the banned organization or association or institution or separatist movement in Indonesian. The above explanation makes the writer interested in aanalysing it further with existing legal theory. The research question is what is the position of the flag and emblem of Aceh in relation to legal justice. What is the influence of the flag and emblem of the province of Aceh in the effort to unite the people of Aceh towards legal certainty. How does the flag and emblem of Aceh influence legal order in Indonesia, and is there any legal utility. The method used is descriptive research analysis which is a study that aims to describe or illustrate systematically, factually and accurately a population or certain regions regarding the nature or certain factors. Research results show that the Qanun made should meet the elements of legal objectives in order to be more beneficial to the community at large.